MOF-71 as a degradation product in single crystal to single crystal transformation of new three-dimensional Co(ii) 1, 4-benzenedicarboxylate. Issue 1 (25th November 2015) - Chisca, Diana; Croitor, Lilia; Petuhov, Oleg; Coropceanu, Eduard B.; Fonari, Marina S.
Abstract : The single crystal to single crystal transformation of an unknown three-dimensional cobalt(ii ) terephthalate to MOF-71 is reported. Abstract : A new three-dimensional coordination polymer, [Co(μ2 -H2 O)(bdc)(H2 O)(dmf)]·0.5H2 O n (1 ), was obtained as a by-product in the synthesis of the laminar solid [Co2 (μ2 -H2 O)(bdc)2 (S-nia)2 (H2 O)(dmf)]·(dmf)2 ·H2 O n (2 ) (where H2 bdc = 1, 4-benzenedicarboxylic acid, S-nia = thionicotinamide, dmf = N, N ′-dimethylformamide). The three-dimensional network in1 is organized of Co(ii ) atoms in O6 octahedral coordination environments separated by μ2 -water molecules in coordination chains. The bdc 2− anions coordinate in monodentate mode and also act as bridging ligands that extend the structure in two other directions. The coordination cores of two crystallographically different Co(ii ) atoms are completed by either two dmf or two water molecules. The rhombohedral open channels contain water molecules. The evacuation of solvents from1 occurs as a single crystal to single crystal transformation and results in MOF-71, [Co(bdc)(dmf)] n, whose structure was confirmed by single crystal X-ray diffraction.